2010
DOI: 10.1002/hep.23440
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide‐binding oligomerization domain containing 2 (NOD2) variants are genetic risk factors for death and spontaneous bacterial peritonitis in liver cirrhosis†

Abstract: S pontaneous bacterial peritonitis (SBP) is a frequent and severe complication of cirrhosis. As a marker of severe hepatic dysfunction, SBP occurs in up to 30% of patients with cirrhosis and ascites. 1 The survival of patients with liver cirrhosis who recover from a first episode of SBP is significantly reduced and despite antibiotic treatment, SBP is still associated with in-hospital mortality rates between 15% and 30%. [2][3][4] The term SBP was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
2
11

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 130 publications
(114 citation statements)
references
References 40 publications
2
98
2
11
Order By: Relevance
“…It seems that the presence of bacterial DNA in serum and ascitic fluid is an independent factor in noninfected patients with the cirrhosis and implies a poor prognosis [15,29]. Recent studies suggest that a genetic variant associated with impaired mucosal barrier function may also be involved in this process [30]. …”
Section: Discussionmentioning
confidence: 99%
“…It seems that the presence of bacterial DNA in serum and ascitic fluid is an independent factor in noninfected patients with the cirrhosis and implies a poor prognosis [15,29]. Recent studies suggest that a genetic variant associated with impaired mucosal barrier function may also be involved in this process [30]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, essentially all animal models of intestinal fibrosis appear to be dependent on the presence of a microflora to initiate or perpetuate gut inflammation and fibrosis [25]. Although direct evidence about the innate immunity gene variants in liver fibrosis is lacking, several studies have shown that NOD2 is associated with the increased mortality in nonalcoholic liver transplant patients [30] or the increased risk of spontaneous bacterial peritonitis in patients with liver cirrhosis [31,32]. …”
Section: Innate Immunitymentioning
confidence: 99%
“…Genetic factors may be involved in the development of infection-related ACLF. Genetic variants commonly found in Crohn's disease occur in patients with cirrhosis [21]. An intriguing finding is that the presence of these genetic variants in cirrhotics is associated with a high risk of death [21].…”
Section: Mechanisms Of Infection-related Aclfmentioning
confidence: 99%